IMPLEMENTASI PENGUATAN NILAI KARAKTER NASIONALISME DI SMK NEGERI 1 ENTIKONG PERBATASAN KALIMANTAN BARAT - Sulanda, Sulanda; Sulistyarini , Sulistyarini; Admaja , Thomy Sastra; Mashudi , Mashudi; Purnama , Shilmy (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The purpose of this study was to determine the implementation of strengthening the character of nationalism at SMK Negeri 1 Entikong in the border area of Entikong, West Kalimantan. This research uses a qualitative approach with descriptive methods. The subjects in this study were the Principal, Deputy Head of Student Affairs, Civics Teacher, Counseling Teacher and students of SMK Negeri 1 Entikong. The informants of this research were determined by purposive sampling technique. Data collection was conducted using interview, observation, and documentation techniques. Data analysis was conducted using the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results showed that strengthening the character of nationalism through routine activities in the form of flag ceremonies every Monday, singing national songs before starting learning, playing national songs in the school environment, and extracurricular activities of scouts, paskibra, PMR and State Defense coaching activities by members of the TNI. Spontaneous activities in the form of teacher actions reconcile students who are fighting, teachers reprimand students who insult ethnicity, religion, race and intergroup, teachers punish students who bully, teachers and students make donations if there are school residents who are grieving or affected by a disaster, and school residents visit sick students or teachers. Exemplary activities in the form of teacher behavior that does not differentiate between ethnicity, religion, race and intergroup, and the social status of their students, polite teacher speech, not rude and not rude.